Interactions between law enforcement and women of color at high-risk of lethal intimate partner violence: An application of interpersonal justice theory - Harper, Shannon B. (Criminal justice studies, 2021)
Research suggests that women of color (WOC) survivors are often dissatisfied with police response to their calls for intimate partner violence (IPV) assistance due to disrespectful, apathetic, and rude treatment. A strong empirical relationship exists between severity of abuse and police help-seeking among WOC survivors more generally; however, scarce literature exists examining the nature of interactions between officers and WOC survivors during life-threatening abuse situations. This study contributes to the literature by examining WOC's satisfaction with law enforcement response within an interpersonal justice framework, and how survivors' “severe abuse contexts” contribute to police help-seeking decision-making. In-depth interviews were conducted with high-risk WOC IPV survivors. Results revealed two themes that describe participants’ perceptions of police treatment as dismissive/lethargic (T1) and hostile/callous (T2). Findings suggest that unfair treatment from officers has dangerous implications for ongoing survivor safety among WOC. Non-carceral IPV prevention and survivor safety enhancement perspectives are also discussed.